Miracles on Maple Hill - Sorensen, Virginia, 1912-1991.; Krush, Beth; Krush, Joe (Orlando, Fla. : Harcourt, 2003)
After her father returns from the war moody and tired, Marly's family decides to move from the city to Maple Hill Farm in the Pennsylvania countryside where they share many adventures which help restore their spirits and their bond with each other.
"An Odyssey/Harcourt young classic."
Newbery Medal, 1957.
Keywords: Moving, Household -- Fiction; Family problems -- Fiction; Country life -- Pennsylvania -- Fiction; Newbery Medal; Pennsylvania -- History -- 20th century -- Fiction